Liver function tests of HIV/AIDS patients at the nylon district hospital, Douala, Cameroon - Ebot, Walter O.; Achidi, Eric A.; Kamga, Henri-Lucien F.; Njunda, Anna L.; Apinjoh, Tobias O. (International Journal of Research in Medical Sciences, 2017)
Background: Antiretroviral therapy (ART) which substantially reduces morbidity and mortality in human immunodeficiency virus (HIV) seropositive patients has been associated with hepatotoxicity. This study was aimed at investigating the effects of HIV infection and ART on liver function amongst HIV seropositive patients in Douala, Cameroon. Methods: A cross- sectional study was conducted from March to August, 2012 at the Nylon District Hospital, Douala. Demographic data were collected using a structured questionnaire. Serum alanine and aspartate aminotransferases (ALT and AST), alkaline phosphatase (ALP) and gamma glutamyl transferase (GGT) activities were determined using colorimetric techniques. Results: The mean age of the study participants was 37.9 ± 6.02 years. A majority of the study participants (68.0%) were females. The mean CD4+ T lymphocyte cell count of HIV/AIDS patients on ART was significantly higher than the ART- naïve patients (p<0.05). The mean serum AST and ALT activities of ART-naïve patients were significantly higher than the control subjects (p<0.05). Similarly, the mean serum transaminases and GGT activities of HIV/AIDS patients on ART were significantly higher than the control subjects (p<0.05). The mean serum ALP and GGT activities of HIV/AIDS patients receiving ART were significantly higher than the ART- naïve patients (p<0.05). Conclusions: The present study provides evidence to suggest that both infection with HIV and treatment with ART are associated with liver injury.